1986
DOI: 10.3109/02813438609014823
|View full text |Cite
|
Sign up to set email alerts
|

Problem Oriented Participatory Education in the Guidance of Adults with Non-insulin-treated Type-II Diabetes Mellitus

Abstract: A population-based study on the therapeutic effects of a diabetes teaching programme (DTP) based on problem oriented participatory education (POPE)--a method based on learner activity in group meetings--was undertaken at the Primary Health Care Centre, Kisa, Sweden, in collaboration with educationalists. A control group was given conventional classroom teaching. To be included a patient had to be aged 55-73 years, to live in his own home, and to have non-insulin-treated type II diabetes mellitus. The therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Among studies with shorter follow-up duration, Wood (54) noted an increase in physical activity at 4 months, Glasgow et al (74) found an increase in the number of minutes of activity 3 months after an intensive intervention, and Wierenga (75) found improved physical activity after five intervention sessions at 4 months. Five studies found no changes in physical activity compared with control groups (30,40,69,76,77). It is unclear what factors might account for success in some studies and not in others.…”
Section: Lifestyle Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among studies with shorter follow-up duration, Wood (54) noted an increase in physical activity at 4 months, Glasgow et al (74) found an increase in the number of minutes of activity 3 months after an intensive intervention, and Wierenga (75) found improved physical activity after five intervention sessions at 4 months. Five studies found no changes in physical activity compared with control groups (30,40,69,76,77). It is unclear what factors might account for success in some studies and not in others.…”
Section: Lifestyle Behaviorsmentioning
confidence: 99%
“…Most studies with positive results involved regular contacts or reinforcement sessions (38,47,66,76,82,84) or very short follow-up periods (72,74), although four studies had follow-up periods of Ն5 months (36,38,80,82). All other studies with follow-up of Ն6 months after the end of the intervention failed to show significant differences in weight loss between control and interventiongroups (30,31,61,65,71,73,77,79,84,87,88,90,91). A number of other studies with shorter follow-up periods also had combined I-1 and I-2 C: Relaxation training to cope with stress All groups got nine weekly sessions of 1.5 h BL, baseline; BS, blood sugar; BP, blood pressure; C, C-1, C-2, control groups; CAI, computer-assisted instruction; CHO, carbohydrate; D/SBP, diastolic/systolic blood pressure; DM, diabetes mellitus; DM2, type 2 diabetes; FBS, fasting blood sugar; F/U, follow-up; HCW, health-care worker; I, I-1, I-2, I-3, intervention groups; IP, inpatient; NSD, no significant difference; OP, outpatient; PA, physical activity; q, every; RN, registered nurse; SD, significant difference; TC, telephone call.…”
Section: Cardiovascular Disease Risk Factorsmentioning
confidence: 99%
“…In one study variance was calculated from the P value (50). If only the range was given as the measure of variation, then the SD was calculated as the range divided by 5.88 (6 SDs) (28). In several studies, the measure of variance was unclear or was assumed to be labeled incorrectly.…”
Section: Data Extractionmentioning
confidence: 99%
“…If a study had several different intervention groups, we averaged GHb and variances within each study, weighted by the sample size (8,27,30,38,(41)(42)(43)(44)(45)(46). In several studies, GHb point estimates and CIs were not presented in numeric form, and they were estimated from graphs (28,30,47,48). If the SE was missing for the control or intervention groups at baseline or followup, then it was assumed to be the same as the value reported for the other group (27,29,30,42,43,49).…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation